(untitled) (Fourth World Journal, 2024)
This article was originally published in Vol. 13, No. 2, Winter 2015. Fourth World knowledge systems vary widely but in the contemporary international environment nations may be seen as engaging neighboring nations, states and international institutions with differing capacities. Understanding the different diplomatic capacities and levels of knowledge is critical to the process of implementing the UN Declaration on the Rights of Indigenous Peoples (UNDRIP). Mechanisms for implementing the UNDRIP must be nation specific and state specific agreeable to both sides. Forty or more years after “indigenous rights” was sounded as a human rights goal, and indigenous nations are now obliged to take diplomatic initiatives employing their history of diplomatic experience.